Metabolic Activity in Central Neural Structures of Patients With Myocardial Injury - Michael Fiechter; Andrea Roggo; Achi Haider; Susan Bengs; Irene A. Burger; Monika Marędziak; Angela Portmann; Valerie Treyer; Anton S. Becker; Michael Messerli; Urs J. Mühlematter; Ken Kudura; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Increasing evidence suggests a psychosomatic link between neural systems and the heart. In light of the growing burden of ischemic cardiovascular disease across the globe, a better understanding of heart‐brain interactions and their implications for cardiovascular treatment strategies is needed. Thus, we sought to investigate the interaction between myocardial injury and metabolic alterations in central neural areas in patients with suspected or known coronary artery disease. Methods and Results The association between resting metabolic activity in distinct neural structures and cardiac function was analyzed in 302 patients (aged 66.8±10.2 years; 70.9% men) undergoing fluor‐18‐deoxyglucose positron emission tomography and 99mTc‐tetrofosmin single‐photon emission computed tomography myocardial perfusion imaging. There was evidence for reduction of callosal, caudate, and brainstem fluor‐18‐deoxyglucose uptake in patients with impaired left ventricular ejection fraction (<55% versus ≥55%: P=0.047, P=0.022, and P=0.013, respectively) and/or in the presence of myocardial ischemia (versus normal perfusion: P=0.010, P=0.013, and P=0.016, respectively). In a sex‐stratified analysis, these differences were observed in men, but not in women. A first‐order interaction term consisting of sex and impaired left ventricular ejection fraction or myocardial ischemia was identified as predictor of metabolic activity in these neural regions (left ventricular ejection fraction: P=0.015 for brainstem; myocardial ischemia: P=0.004, P=0.018, and P=0.003 for callosal, caudate, or brainstem metabolism, respectively). Conclusions Myocardial dysfunction and injury are associated with reduced resting metabolic activity of central neural structures, including the corpus callosum, the caudate nucleus, and the brainstem. These associations differ in women and men, suggesting sex differences in the pathophysiological interplay of the nervous and cardiovascular systems.